2018
DOI: 10.1080/09593985.2018.1489926
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ experiences with a blended osteoarthritis intervention: a mixed methods study

Abstract: Determinants related to the usage of e-Exercise provided valuable information for the implementation of e-Exercise on broader scale. Most importantly, the flexibility of e-Exercise needs to be improved. Next, there is a need for education on how to integrate an online program within physiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…An important operational issue is the physiotherapists' training in the e-Exercise LBP intervention. From previous studies we learned that implementing a blended intervention into daily routine is a complex process that changes existing routines [28]. Therefore, training of the participating physiotherapists in the e-Exercise LBP intervention has been expanded from a 4-h training session to two 4-h training sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important operational issue is the physiotherapists' training in the e-Exercise LBP intervention. From previous studies we learned that implementing a blended intervention into daily routine is a complex process that changes existing routines [28]. Therefore, training of the participating physiotherapists in the e-Exercise LBP intervention has been expanded from a 4-h training session to two 4-h training sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all these benefits, matching the appropriate blended treatment for the individual patient is reported as a challenge [28]. To resolve this challenge within traditional face-to-face guidance, stratification tools have gained more attention in the last decade.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Recent studies showed the potential of a blended care delivery mode, in which physiotherapy sessions are integrated with a smartphone application to stimulate patients' ability to manage their musculoskeletal problems independently, outside of treatment sessions [17][18][19]. An example of a blended physiotherapy intervention is e-Exercise, which has been developed for patients with hip and knee osteoarthritis, low back pain, and recently for neck and/or shoulder complaints (van Tilburg M, Kloek CJJ, Pisters MF, Staal JB, Ostelo WJG, Foster NE, et al: Development & feasibility of a stratified approach integrated with eHealth in patients with neck and/or shoulder complaints, in preparation); [17][18][19][20][21]. E-Exercise is an integration of physiotherapy sessions with a smartphone application consisting of an information module, an exercise module, and a physical activity module.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such behavior change techniques are goal setting, assignments, tailored feedback, self-monitoring, visualization of treatment progress and content matching [22]. These behavior change techniques were found to enhance healthy behavior, such that recurrences of symptoms might be prevented, which might in turn lead to a reduction in healthcare and societal costs [21,23]. However, blended care may not be suitable for every patient and is not expected to be effective in this subgroup [16].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Choice of a specific method of physical therapy or physiotherapy exercises should always take into account both the clinical condition of the patient and the physiotherapist's experience. [9] The use of analgesics improves the quality of life of patients but their long-term application can lead to many side effects (toxic effects on the liver and kidneys, hematopoietic system, and gastrointestinal mucosa), and also involves the cost of medication. Thorlund et al [10] showed that chronic (over 1 year) use of analgesics in patients with osteoarthritis of knee and hip joints affected the exacerbation of symptoms of comorbidities in the treated group of patients.…”
Section: Introductionmentioning
confidence: 99%